The bride of Lammermoor - Scott, Walter (b, 2009)
The Waverly novels by the immensely popular Scottish author enthralled readers with their dashing mix of historical fiction, romance, and revenge. This installment, originally published in 1819, takes place in the early 1700s and tells of a doomed love affair between a young woman and her family's sworn enemy. The tale served as the inspiration for Donizetti's opera Lucia di Lammermoor"--
Keywords: Arranged marriage -- Fiction; Scotland -- Fiction